Meningkatkan Minat Belajar Bahasa Indonesia Menggunakan Media Berbasis Teknologi Educaplay Pada Siswa Kelas XI IPS SMA IT Izzuddin Palembang - L, Lathifah; Lestari, Hikmah; Fitriani, Yessi; Lestari, Rizcha Fuji (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aimed to improve the learning interest of eleventh-grade social science students at SMA IT Izzuddin Palembang in the Indonesian Language subject through the use of the Educaplay technology-based learning media. This research was a Classroom Action Research (CAR) conducted in two cycles. Data collection was carried out through observations, questionnaires, and documentation. The results showed an increase in students' learning interest based on observations and questionnaire results. In the pre-research stage, the observation results showed that students' learning interest was still low (48%). After implementing Educaplay in cycle I, the observation results of students' learning interest increased to 70% (moderate), and in cycle II, it increased to 85% (high). Meanwhile, based on the questionnaire, students' learning interest in cycle I was in the moderate category (71%), and in cycle II, it increased to 83% (high). It can be concluded that the use of the Educaplay learning media can improve the Indonesian language learning interest of eleventh-grade social science students at SMA IT Izzuddin Palembang.